The Role of Pulmonary Artery Wedge Pressure on the Incidence of Atrial Fibrillation and Atrial Tachycardias in Patients With Isolated Pre-capillary Pulmonary Hypertension - Dusík, Milan; Fingrová, Zdeňka; Ambrož, David; Jansa, Pavel; Linhart, Aleš; Havránek, Štěpán (Physiological research, 2021)
Atrial fibrillation and atrial tachycardias (AF/AT) have been reported as a common condition in patients with pulmonary hypertension (PH). As yet, limited data exists about the significance of the borderline post-capillary pressure component on the occurrence of AF / AT in patients with isolated pre-capillary PH. We retrospectively studied the prevalence of AF / AT in 333 patients (mean age 61 ± 15 years, 44% males) with pre-capillary idiopathic / familiar pulmonary arterial hypertension, and inoperable chronic thromboembolic pulmonary hypertension. The prevalence of AF / AT was analyzed in different categories of pulmonary artery wedge pressure (PAWP). In the study population overall, the mean PAWP was 10.5 ± 3 mmHg, median of 11 mmHg, range 2-15 mmHg. AF / AT was diagnosed in 79 patients (24%). The proportion of AF / AT among patients with PAWP below the median (?11 mmHg) was lower than in subjects with PAWP between 12 and 15 mmHg, 30 (16%) vs. 46 (35%), p = 0.0001. Compared to the patients with PAWP?11 mmHg, subjects with PAWP between 12 and 15 mmHg were older (65 ± 13 years vs. 58 ± 16), with more prevalent arterial hyperte\nsion [100 (70%) vs. 106 (55%)] and diabetes mellitus [50 (35%) vs. 48 (25%)], showed larger size of the left atrium (42 ± 7 vs. 40 ± 6 mm), and higher values of right atrium pressure (12 ± 5 vs. 8 ± 5 mm Hg), p < 0.05 in all comparisons. The prevalence of AF / AT in the group studied increased with the growing post-capillary component.
Keywords: dospělí; Female; Pulmonary Wedge Pressure; Prevalence; Atrial Fibrillation; Hypertension, Pulmonary; Adult; ženské pohlaví; plicní tlak v zaklínění; Registries; lidé; síňová ektopická tachykardie; Incidence; prevalence; retrospektivní studie; Male; incidence; Aged; Czech Republic; Tachycardia, Ectopic Atrial; plicní hypertenze; Česká republika; fibrilace síní; lidé středního věku; registrace; senioři; mužské pohlaví; Retrospective Studies; Middle Aged; Humans